Նամակներ թերյիշեալ երախտաւորէ մը՝ բժիշկ Գրիգոր Դաւիթեան (1866-1924) - Ղազարեան, Վաչէ (տպ. Atlas)
In three letters published for the first time, Dr. Tavitian, Chairman of the Political Council of the Armenians in Turkey during the aftermath of the armistice in 1918, touches upon matters related to the Armenian Question, the reorganization of Armenian leading authorities, the chaotic and insecure atmosphere in post-WWI Ottoman Tukey, the inaction of the Allied Powers to mitigate the threats to surviving Armenians, news of the massacre of Armenians in Aleppo, the initiation of Armenian-Kurdish negotiations, and so on.
Keywords: Նամակներ; Պատմութիւն